A Control Chart for COM–Poisson Distribution Using Multiple Dependent State Sampling. (18th February 2016) - Aslam, Muhammad; Ahmad, Liaquat; Jun, Chi‐Hyuck; Arif, Osama H.
Abstract : In this article, an attribute control chart has been proposed for the COM–Poisson distributed non‐conformities using multiple dependent states sampling based on the exponentially weighted moving average statistic. Average run lengths of the out‐of‐control process with different shift levels of the COM–Poisson distribution have been calculated through simulation. From comparison, it has been observed that the proposed control chart is better in detecting the out‐of‐control process quickly as compared with the existing control chart. A simulated example has been given for the practical use of the proposed control chart. Copyright © 2016 John Wiley & Sons, Ltd.